2009
DOI: 10.1021/ie9000162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Coal Interaction with Supercritical CO2: Physical Structure

Abstract: It is known that polar solvents swell coal, break hydrogen-bonds in the macromolecular structure, and enhance coal liquefaction efficiencies. The effects of drying, interaction with supercritical CO2 and degassing on the physical structure of coal have been studied using gas sorption technique and a scanning electron microscope (SEM). Both drying and interaction with supercritical CO2 drastically change the micropore and mesopore surface area, absolute volume, and volume distribution in both bituminous coal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(81 citation statements)
references
References 14 publications
6
75
0
Order By: Relevance
“…This conclusion is consistent with other investigations. Applying both adsorption and scanning electron microscopy (SEM) methods, Gathitu et al 58 found that CO 2 exposure cannot significantly change the micropore surface and volume of dry bituminous coal. Kutchko et al 59 also concluded that CO 2 exposure made no obvious change to the pore structure of Pittsburgh and Sewickly coal samples, according to fieldemission scanning electron microscopy (FE-SEM) analysis.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…This conclusion is consistent with other investigations. Applying both adsorption and scanning electron microscopy (SEM) methods, Gathitu et al 58 found that CO 2 exposure cannot significantly change the micropore surface and volume of dry bituminous coal. Kutchko et al 59 also concluded that CO 2 exposure made no obvious change to the pore structure of Pittsburgh and Sewickly coal samples, according to fieldemission scanning electron microscopy (FE-SEM) analysis.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…Coal has a strong affinity for CO 2 , and interactions with supercritical CO 2 can drastically change the micropore and mesopore surface area, absolute volume, and volume distribution in both bituminous coal and lignite. After interaction with supercritical CO 2 , micropore surface area and volume is observed to grow (Gathitu et al 2009), but mesopore and macropore surface area and volume increase drastically (Liu et al 2010). In the Yaojie coalfield, supercritical CO 2 is likely to exist in the NO.…”
Section: Discussionmentioning
confidence: 97%
“…After interaction with supercritical CO 2 , micropore surface area and volume is observed to grow (Gathitu et al . ), but mesopore and macropore surface area and volume increase drastically (Liu et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…During the process of CO 2 -ECBM, CO 2 is distributed into the coal seam through the coal cleat system and then stored within the coal matrix due to the stronger affinity between CO 2 and the coal substance [9][10][11]. Previous studies have also shown that there are various physical and geochemical interactions between CO 2 and coals, such as gas adsorption on the coal 2 of 11 internal surface [9][10][11][12][13][14], coal matrix swelling due to gas adsorption [15][16][17], and CO 2 reaction with minerals [18][19][20].…”
Section: Introductionmentioning
confidence: 99%